Observation of Weyl nodes and Fermi arcs in tantalum phosphide - N. Xu (Nature Portfolio, 2016)
Weyl semimetals exhibit exotic properties owing to the presence of Weyl fermions. Here, Xu et al. show that tantalum phosphide is an ideal platform for studying the transport properties of these particles because its low-energy properties are dominated by a single type of Weyl fermion.